PENANGANAN SAMPAH DI TEMPAT WISATA PANTAI X TAHUN 2023 - Puspita, Lista; Karmini, Mimin (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2024)
X Beach is one of the most popular tourist attractions. Apart from being economically valuable, tourism activities can also generate waste. For this reason, proper waste management is needed so that it does not have a negative impact on the environment and health. The aim of the study was to determine waste generation, the level of knowledge of traders and cleaners, the waste handling stages of sorting, container, collection, transportation, infrastructure and waste reduction with the 3R principle. The population consists of 30 traders and 5 janitors. The samples of traders and janitors were taken as a whole. Data collection techniques by weighing, interviewing and observation. Scales data collection tools, questionnaires, observation sheets, cameras. Univariate data analysis. The results of the research on waste generation for 8 consecutive days were 196.8 Kg/day with an average of 24.6 Kg/day, the level of knowledge of traders was 40% in the Good category, the cleaners were 100% Good. The sorting stage for traders and waste workers is 100% not fulfilling the requirements, the container stage for traders is 90% fulfilling the requirements and by cleaning staff 100% is not fulfilling the requirements. The temporary collection stage of 100% waste does not meet the requirements. The 100% waste transportation stage does not meet the requirements. Facilities and infrastructure 100% do not meet the requirements. Reduce waste from the source by creating a waste bank to get waste that has economic value.